Hippocampal dendritic spines remodeling and fear memory are modulated by GABAergic signaling within the basolateral amygdala complex - Giachero, Marcelo (2015)
GABAergic signaling in the basolateral amygdala complex (BLA) plays a crucial role on the modulation of the stress influence on fear memory. Moreover, accumulating evidence suggests that the dorsal hippocampus (DH) is a downstream target of BLA neurons in contextual fear. Given that hippocampal structural plasticity is proposed to provide a substrate for the storage of long-term memories, the main aim of this study is to evaluate the modulation of GABA neurotransmission in the BLA on spine density in the DH following stress on contextual fear learning. The present findings show that prior stressful experience promoted contextual fear memory and enhanced spine density in the DH. Intra-BLA infusion of midazolam, a positive modulator of GABAa sites, prevented the facilitating influence of stress on both fear retention and hippocampal dendritic spine remodeling. Similarly to the stress-induced effects, the blockade of GABAa sites within the BLA ameliorated fear memory emergence and induced structural remodeling in the DH. These findings suggest that GABAergic transmission in BLA modulates the structural changes in DH associated to the influence of stress on fear memory.